3D printing approaches to simulate natural diets for insects with implications for domestication and mass-rearing - Pascacio-Villafán, Carlos; Tejada-Ortigoza, Viridiana; Cohen, Allen Carson; Aluja, Martín (Frontiers in Insect Science, 2025)
Many insect species that could benefit humanity cannot be reared or domesticated because of the lack of adequate artificial diets. In the case of insect pests which are controlled via the Sterile Insect Technique, the prospects of improving biological traits of mass-reared individuals hinge on the development of new diet formulations. 3D food printing technology holds unique potential to create customized artificial diets simulating the shape, texture, and distribution of nutrient and non-nutrient components (e.g., dietary fiber and secondary metabolites) of natural insect foods. We present an overview on the use of state-of-the-art 3D printing technology to develop artificial diets that mimic the dynamic nature of natural insect diets, characterized by compartmentalized food components. The challenges and limitations of 3D food printing technology for its application in the field of diet development and artificial insect rearing are discussed, and future research priorities are highlighted. Examples are provided of beneficial and pestiferous insect species that could be reared on 3D-printed diets such as the cocoa pod borer and tephritid flies.